Peningkatan Kapasitas Masyarakat melalui Pelatihan Kesehatan Lingkungan dan Keselamatan Kerja di Kawasan Padat Penduduk Kelurahan Murante, Kecamatan Mungkajang - Anggreni, Iin; Zamly (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2025)
Household-based environmental health and occupational safety (OHS) training is a crucial intervention in improving the quality of life for communities in densely populated areas. This community service activity was conducted over seven days in Neighborhood Association (RW) 04, Murante Village, Mungkajang District, Palopo City. The activity included education, field practice, simulations, and the formation of environmental OHS cadres. Evaluation results showed significant improvements in participants' knowledge (60% to 85%), skills (55% to 82%), and attitudes (58% to 84%). Furthermore, five environmental and OHS cadres were formed, who became agents of change in the community. This activity demonstrates that a participatory and educational approach can increase community capacity in creating a healthy and safe environment.